The Utilization of the Wokwi Simulator Platform as a STEM Learning Innovation in the Internet of Things (IoT) Course - St. Munthakhabah R, Cita; Wahid, Anwar; Muh Zulfardinsyah, Laode; Zam’ah, Zam’ah; Nurhuda, Nurhuda (IJORER : International Journal of Recent Educational Research, 2026)
The purpose of this study is to examine the use of the Wokwi Simulator Platform as a STEM-based learning innovation in Internet of Things (IoT) courses in higher education. This study uses a qualitative approach with a single instrumental case study design involving 24 undergraduate students from one IoT practicum class at the Information Technology Education Study Program, University of West Sulawesi, in the period September–October 2025. Data were collected through semi-structured interviews, participatory observations, and learning documentation, and then analysed using the interactive analysis model Miles, Huberman, and Saldaña. The results revealed three main interrelated themes. First, the efficiency and flexibility of using Wokwi allows students to conduct repeated experiments without hardware limitations, thus encouraging the formation of active experimentation. Second, the virtual debugging process directs students to focus more on programming logic and scientific reasoning, thus strengthening the reflective observation stage. Third, holistic STEM integration is reflected through the use of real-time data visualisation features that help students understand the interconnectedness of cross-disciplinary concepts in the abstract conceptualisation stage. In the context of previous research on virtual labs and STEM-based IoT learning, these findings expand existing studies by presenting qualitative empirical evidence on how simulated environments support experiential learning processes rather than simply improving learning outcomes. This study concludes that the Wokwi Simulator Platform functions as an effective pedagogical medium in supporting STEM-oriented IoT learning, especially in the context of higher education with limited laboratory resources. These findings provide implications for designing IoT curricula that emphasise data-driven analysis and interdisciplinary integration, and further research is needed to examine the transfer of learning from virtual simulations to physical hardware implementations.